Assessment of reliability of secondary traits in selecting for improved grain yield in drought and lownitrogen environments - Badu-Apraku, Baffour; Akinwale, R.; Franco, J.; Oyekunle, M. (Wiley, 2012)
Grain yield of maize (Zea mays L.) has low heritability under low soil nitrogen (low N) and drought, necessitating the use of secondary traits with strong associations with yield forselection. A base index involving anthesis– silking interval, plant and ear aspects, earsper plant, and stay green characteristic is used for selection for yield under drought and low-N stresses. Reports are contradictory on the reliability of stay green characteristic for selecting for yield under drought stress and of ears per plant and anthesis–silking interval in selecting for low-N tolerance. Ninety extraearly inbreds were evaluated for 2 yr at three locations in Nigeria under low N and drought to confi rm reliability of stay green characteristic for selecting for drought tolerance and of ears per plant and anthesis–silking interval for low N. Plant aspect and plant and ear heights were identifi ed as the most reliable traits for simultaneous selection for yield under low N and drought in the extra-early inbreds. Stay green characteristic was unreliable for selecting drought tolerant genotypes while ears per plant and anthesis–silking interval were not among the reliable traits for selecting low-N tolerant genotypes. Ear height, plant and ear aspects, and stay green characteristic were identifi ed by both path–coeffi cient and genotype main effect plus genotype × environment interaction (GGE) biplot analyses as reliable for selecting for low N and ear aspect, plant height, and anthesis–silking interval for drought tolerance.